2018
DOI: 10.1074/jbc.ra118.002352
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the loss-of-function effects of the Alzheimer's disease–associated R47H variant of the immune receptor TREM2

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) is an immune receptor expressed on the surface of microglia, macrophages, dendritic cells, and osteoclasts. The R47H TREM2 variant is a significant risk factor for late-onset Alzheimer's disease (AD), and the molecular basis of R47H TREM2 loss of function is an emerging area of TREM2 biology. Here, we report three high-resolution structures of the extracellular ligand-binding domains (ECDs) of R47H TREM2, apo-WT, and phosphatidylserine (PS)-bound WT TREM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(157 citation statements)
references
References 34 publications
(56 reference statements)
15
142
0
Order By: Relevance
“…2.A). Part of this region comprises a phospholipid binding surface identified in a recent co-crystal structure [16], and computational analyses have suggested that the stability of this binding surface may be disrupted by variants associated with neurodegenerative diseases, including AD risk variants [35]. Remarkably, we found that point mutations to this surface (M41D, W44D, L69D, W70D, and F74D) decreased binding affinity for ApoE4 by 5-200-fold ( Fig.…”
Section: Trem2 Ad Variants Subtly Alter Apoe Binding While Mutations supporting
confidence: 51%
See 2 more Smart Citations
“…2.A). Part of this region comprises a phospholipid binding surface identified in a recent co-crystal structure [16], and computational analyses have suggested that the stability of this binding surface may be disrupted by variants associated with neurodegenerative diseases, including AD risk variants [35]. Remarkably, we found that point mutations to this surface (M41D, W44D, L69D, W70D, and F74D) decreased binding affinity for ApoE4 by 5-200-fold ( Fig.…”
Section: Trem2 Ad Variants Subtly Alter Apoe Binding While Mutations supporting
confidence: 51%
“…We found that point mutations to a distal hydrophobic surface composed of the CDR1-3 loops on TREM2 reduced binding to ApoE by about 10-1000-fold. It is worth noting that a recent crystal structure of the TREM2 R47H variant [16] and results from molecular dynamics simulations of TREM2 R47H, R62H, and T96K variants [35] show that these AD risk variants induce structural instability in the CDR2 loop, which comprises a central portion of this hydrophobic patch. Thus, these structurally-induced impacts on the hydrophobic patch could explain why TREM2 basic patch mutations display moderate decreases in binding to ApoE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we did not observe profound difference in the differentiation and maturation propensity between iPSCs derived from LOAD patients and healthy donors-in agreement with previous reports (Flamier et al, 2018;Hossini et al, 2015;Israel et al, 2012;Ochalek et al, 2017). Cheng-Hathaway et al, and Sudom et al, reported that Trem2 R47H knock-in mice showed reduced Trem2 mRNA and protein expression in the brain as well as reduced soluble fragments of Trem2 (sTrem2) in plasma (Cheng-Hathaway et al, 2018;Sudom et al, 2018). More recently, Xiang et al…”
Section: Discussionsupporting
confidence: 92%
“…Reduced solubility, increased turnover, altered glycosylation, and reduced sTREM2 shedding of the R47H variant had previously been reported in cell culture and in vivo. Thus, the new structural data can shed some light on how these are connected (Park et al, 2015;Park, Ji, Kim, An, & Yoon, 2017;Sudom et al, 2018).…”
Section: Trem2 Loss-of-function Mutations Are Associated With Neuromentioning
confidence: 99%